Business statistics demystified - Kemp, Steven M. 4 0 16; Kemp, Sid; 5 (New York : McGraw-Hill, 2004)
Presents a comprehensive self-teaching guide to business statistics and includes quizzes and tests as well as tips on terminology, concepts, and equations.
A self-teaching guide--Cover.
Includes bibliographical references (p. 367) and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Commercial statistics.;Statistics. -- 20; 20; 2